LEARNING STRATEGIES IN WRITING PROCEDURE TEXT USED BY THE VIII GRADE STUDENTS - Lebrina Mundi; Abdul Kamaruddin (Tadulako University, 2021)
The objectives of this research was to find out the learning strategies in writing procedure text and to know about the students reasons for using those strategies by VIII grade students at SMP Negeri 2 Banawa Selatan. The subject of this research was VIII grade students at SMP Negeri 2 Banawa Selatan which the total number 104 students consist of four classes. 21 students were taken as the sample used simple random sampling. Researcher conducted this research using qualitative research types and data collecting used questionnaire and interview. The result of questionnaire shows that in writing procedure text most of the students use strategies in learning such as cognitive strategies, metacognitive strategies, memory related strategies, compensatory strategies, affective strategies, and social strategies. Based on the result of interview session, it can be concluded that the reasons of the students for using these strategies because they want to write procedure text well. The most dominant used learning strategies by the subjects is cognitive strategy. Majority of the subjects more frequently use this strategy among all of strategies in learning procedure text.